Validasi Media Pembelajaran Menulis Cerpen Berbasis Web Kultural - Agnes Apryliana; Hany Uswatun Nisa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to describe the validity of learning media to write short stories. The research method used is descriptive qualitative. The results of this study indicate that the learning media developed are feasible and effective for use in the learning process. The feasibility is seen from the assessment of material, media, and media users' responses with a mean score of 81.25% and in the